Uji Efektivitas Ekstrak Bakteri Simbion Lamun Enhalus sp. Sebagai Bioinsektisida Pada Kecoa Blatella Germanica Di Laboratorium - Farid Masum Fauzi; - Sulistiyani; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Cockroach is a vector disease that lives in the home, restaurants, hotels, hospitals, warehouses, offices, libraries, and others. This insect is very close to human life. The way to control cockroach Blatella germanica is used of insecticides. Biological insecticides is one alternative vector control. Results photochemical content of active compounds contained in the seagrass bacteria Enhalus sp. such as terpenes, alkaloids and carotenoids that can be toxic to insects as an insecticide. This study was aimed to determine the effectiveness of bacterial symbionts of seagrass extracts Enhalus sp. as bioinsektisida on Blatella germanica cockroaches. The research was conducted in April-August 2013. The samples used for this study is isolate bacterial symbiont of seagrass Enhalus sp. Blatella germanica and cockroaches. Methods used are experimental laboratories. The number of samples used for this study is 920 crawly things. Based on probit analysis are obtained at a concentration of LC50 78.203% and LC90 88.078% present in concentrations. based on the results of ANOVA were no significant differences of various concentrations of bacterial extract as seagrass Enhalus sp bioinsektisida Blatella germanica cockroaches to death with a significance of p = 0.000. Communities can apply bacterial symbionts of seagrass extracts Enhalus sp. as bioinsektisida to kill a cockroach so as to reduce the number of diseases caused by cockroaches